The impact of treatment and time on cardiovascular risk scores - Liew, S (2012)
Cardiovascular risk scores predict an individual’s risk of developing cardiovascular disease. Many were developed and validated in study cohorts on risk-factor lowering treatment – a cause of inaccuracy. In addition, risk scores are criticised as being biased towards the elderly due to the prominence of age as a risk predictor. Although present guidelines advocate the use of short-term (5-10 year) absolute risk scores, other approaches to redress this perceived imbalance such as lifetime risk scores are being considered. The overall objective of this thesis is to identify the most appropriate cardiovascular risk score for use in general practice, taking account of the impact of treatment and time on assessed risk. This objective was met by three different methods. First, a systematic review of cardiovascular risk scores was conducted. This explored the derivation of each score, including the extent of treatment. Next, doctors were interviewed in depth to understand their perception and use of risk scores. Finally, mathematical models were devised to determine whether a true difference in life expectancy exists at different ages but the same short-term cardiovascular risk. The models incorporated age-specific case fatality rates, competing risks and time preference to estimate the potential years of life lost due to a five-year treatment delay in different age groups with the same short-term coronary heart disease risk. The findings demonstrate that cardiovascular risk scores do not take account of treatment effects. This significantly affects their application in clinical practice. In addition, there is little difference in potential life years lost between ages at the same risk level because of higher case-fatalities in older people. When time preference is considered, any residual case for treating the same level of short-term risk differently at different ages is abolished. The overall conclusion is that the five to ten-year absolute cardiovascular risk score is the most appropriate approach to primary cardiovascular disease prevention. By overestimating risk in the young, other approaches benefit the few at the expense of the many.